2017
DOI: 10.24251/hicss.2017.306
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Framework for Evaluating E Government Systems Success: A Service Ecosystem Approach

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The public value theory was applied to obtain the values of e-government to measure the net benefits of electronic government. The theory of public value has been useful and applied in similar studies such as Deng et al (2018), Agbabiaka (2018), Sterrenberg (2017) to validate several values useful for measuring the net benefits of e-government. This study tilts research on the performance of e-government to a selection of key and important public values.…”
Section: Discussionmentioning
confidence: 99%
“…The public value theory was applied to obtain the values of e-government to measure the net benefits of electronic government. The theory of public value has been useful and applied in similar studies such as Deng et al (2018), Agbabiaka (2018), Sterrenberg (2017) to validate several values useful for measuring the net benefits of e-government. This study tilts research on the performance of e-government to a selection of key and important public values.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the identified shortcomings in the methods [4,6,8,9,[17][18][19][20], it is necessary to consolidate key criteria and supplement the assessment system with new criteria, both quantitative and qualitative.…”
Section: Methodological Issues Of Prioritization Of Information Syste...mentioning
confidence: 99%
“…A study conducted by Kurfali et al (2017), Sterrenberg (2017) aimed at evaluating or the success of the e-government system. The study concluded that usage of e-government platform is a critical factor in its success.…”
Section: E-government System Usagementioning
confidence: 99%